Ag colloids and arrays for plasmonic non-radiative energy transfer from quantum dots to a quantum well. (16th February 2017) - Murphy, Graham P; Gough, John J; Higgins, Luke J; Karanikolas, Vasilios D; Wilson, Keith M; Garcia Coindreau, Jorge A; Zubialevich, Vitaly Z; Parbrook, Peter J; Bradley, A Louise
Abstract: Non-radiative energy transfer (NRET) can be an efficient process of benefit to many applications including photovoltaics, sensors, light emitting diodes and photodetectors. Combining the remarkable optical properties of quantum dots (QDs) with the electrical properties of quantum wells (QWs) allows for the formation of hybrid devices which can utilize NRET as a means of transferring absorbed optical energy from the QDs to the QW. Here we report on plasmon-enhanced NRET from semiconductor nanocrystal QDs to a QW. Ag nanoparticles in the form of colloids and ordered arrays are used to demonstrate plasmon-mediated NRET from QDs to QWs with varying top barrier thicknesses. Plasmon-mediated energy transfer (ET) efficiencies of up to ∼25% are observed with the Ag colloids. The distance dependence of the plasmon-mediated ET is found to follow the same d −4 dependence as the direct QD to QW ET. There is also evidence for an increase in the characteristic distance of the interaction, thus indicating that it follows a Förster-like model with the Ag nanoparticle-QD acting as an enhanced donor dipole. Ordered Ag nanoparticle arrays display plasmon-mediated ET efficiencies up to ∼21%. To explore the tunability of the array system, two arrays with different geometries are presented. It is demonstrated that changing the geometry of the array allows a transition from overall quenching of the acceptor QW emission to enhancement, as well as control of the competition between the QD donor quenching and ET rates.